Managing the risks from high-tech Investments in India: Differential strategies of foreign and domestic venture capital firms - Kshitija Joshi (Journal of Global Entrepreneurship Research, 2018)
The field of technology investing is ridden with dire risks, particularly the ones arising from the presence of asymmetric information among venture capital firms (VCs) and entrepreneurs. The objective of this paper, is to assess the differential strategies devised by the high-technology focused foreign VCs and domestic VCs in negotiating the information risks encountered by them. The sample for the study comprises 70 active VC firms - both foreign and domestic drawn from the Venture Intelligence database. Using the theoretical framework of resource-based view and transactions costs theory and the non-linear data mining technique of Classification and Regression Trees (CART), we first segregate segments of foreign VCs and domestic VCs exhibiting the highest technology focus. Further, we profile each of these segments and compare and explain the differences in the risk management strategies pursued by them. The results from this paper bring to light several interesting findings. To start with, all high-tech focused foreign VCs are not uniform with regards of the risk-management strategies deployed by them. In general, foreign VCs rely on domain specialization, deep sector knowledge and geographic location within India as primary mechanisms of managing information risks. On the contrary, for high-tech focused domestic VCs syndicating with other specialized VCs combined with the opportunity recognition potential of their investment executives with erstwhile founding experience emerges as the core risk-control strategy.
Keywords: 650; High-technology; Information asymmetry risks; Domestic VCs; Foreign VCs; India; Venture capital; Syndication